A high reducing sugar yield at low temperature from microcrystalline cellulose by hydrogenolysis pretreatment followed by solvated electron-assisted hydrolysis. Issue 2 (17th February 2020) - Pakki, Uma Venkata Satish; Atmakuru, Ramesh
ABSTRACT: Commercial microcrystalline cellulose (MCC) was pretreated by hydrogenolysis, followed by solvated electron-assisted hydrolysis in Na/liquid NH3 medium. The reducing sugar (RS) yield achieved was 98% at 2.2 M concentration of Na/liquid NH3 at 120 °C for about 10 min of hydrolysis time. The MCC hydrolysis conditions were optimized by checking the influence of the molar concentrations of Na metal in liquid NH3 at various temperatures and reaction times for the high RS yield. The RS was estimated by the di-nitro salicylic acid (DNSA) method. The hydrolyzed residues and raw MCC were analyzed by infrared spectroscopy (IR), X-ray diffraction (XRD), thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). The crystallinity index of the MCC was significantly decreased from 79.34% to 37.25%. The IR and SEM images and TGA data clearly indicate that the cellulose was completely hydrolyzed.